Training on the Implementation of Online Learning System Applications for Teachers at SMAN 4 Palopo - Rosmiati*, Rosmiati; Ulvah, Ulvah (Riwayat: Educational Journal of History and Humanities, 2023)
Mastery of information technology is very important for a teacher in learning activities at school. One of the supporting factors for improving the quality of learning is mastering the skills of utilizing online learning system applications. The goal to be achieved in this activity is to transfer science and technology by conducting training activities on the application of online learning system applications for teachers at SMA Negeri 4 Palopo. The method of implementing training activities on the application of online learning system applications at SMA Negeri 4 Palopo is by applying lecture and practice methods. The stages are: teachers are given an understanding as well as an introduction to the online learning system application, provide training on the use of zoom, Classroom, and Quiziz applications to teachers, provide assistance for teachers in the context of implementing online learning system applications at school so that the learning process becomes quality. The results of the PKM program activities entitled "Training on the Application of Online Learning System Applications at SMA Negeri 4 Palopo" were able to improve teacher skills in using online learning system applications so as to improve the quality of learning at school. Based on the training program that has been carried out, it can be concluded that the implementation of the training went smoothly and received a positive response from the teacher as a very good trainee and has been skilled in using online learning system applications such as: Zoom, Classroom, and Quiziz.